2020
DOI: 10.1002/chem.202002888
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Oxidative Cross‐Coupling of Electron‐Deficient Polyfluorophenylboronate Esters with Terminal Alkynes

Abstract: We report herein a mild procedure for the copper‐catalyzed oxidative cross‐coupling of electron‐deficient polyfluorophenylboronate esters with terminal alkynes. This method displays good functional group tolerance and broad substrate scope, generating cross‐coupled alkynyl(fluoro)arene products in moderate to excellent yields. Thus, it represents a simple alternative to the conventional Sonogashira reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…The angle between Dipp 2 Im and the trans ‐ i Pr 2 Im ligand is 173.88(7)°. The molecule is further stabilized by π‐stacking [41f,h,51] between the C 6 F 5 ligand and one of the Dipp 2 Im phenyl substituents, as the angle between the best planes through the fluoroaryl ligand and the Dipp 2 Im phenyl substituents is 8.67(9) ° with a distance between the centroids of these two aromatic rings of 3.2402 Å (cf. 3.35 Å in graphite) [52] …”
Section: Resultsmentioning
confidence: 99%
“…The angle between Dipp 2 Im and the trans ‐ i Pr 2 Im ligand is 173.88(7)°. The molecule is further stabilized by π‐stacking [41f,h,51] between the C 6 F 5 ligand and one of the Dipp 2 Im phenyl substituents, as the angle between the best planes through the fluoroaryl ligand and the Dipp 2 Im phenyl substituents is 8.67(9) ° with a distance between the centroids of these two aromatic rings of 3.2402 Å (cf. 3.35 Å in graphite) [52] …”
Section: Resultsmentioning
confidence: 99%
“…These fluorinated building blocks can be introduced into other organic molecules. , A mechanism was proposed where, in the first step, the reaction of Ni­(IMes) 2 ( 57 ) with the fluoroarene leads to an oxidative addition of the C–F bond with formation of trans -Ni­(IMes) 2 F­(Ar F ) ( 57a ; Scheme ). Although an initial “kinetic” C–H bond activation step would explain the regioselectivity of the borylation reaction (borylation occurs at a site adjacent to a hydrogen substituent), such a species could not be observed even at low temperatures.…”
Section: Nickel-catalyzed C–b Bond Formationmentioning
confidence: 99%
“…Marder and Radius et al . reported that a combination of [Cu(OAc) 2 ] with phenanthroline effectively catalyzed the oxidative cross‐coupling of highly fluorinated aryl‐Bpin compounds with terminal alkynes under mild conditions [168] . The reaction of pentafluorophenyl‐Bpin with ethynylbenzene using 1.8 equivalents of Ag 2 O as the oxidant and 2 equivalents of K 3 PO 4 gave the homocoupled alkyne compound as the major product (Scheme 77).…”
Section: Applications Of Fluorinated Aryl Boronates In Organic Synthesismentioning
confidence: 99%
“… Optimization reaction of copper‐catalyzed oxidative cross‐coupling of fluorinated aryl‐Bpin with terminal alkynes [168] …”
Section: Applications Of Fluorinated Aryl Boronates In Organic Synthesismentioning
confidence: 99%